The Influence of Life History on the Response to Parasitism: Differential Response to Non-Lethal Sea Lamprey Parasitism by Two Lake Charr Ecomorphs. (13th January 2022) - Firkus, Tyler J; Goetz, Frederick W; Fischer, Gregory; Murphy, Cheryl A
Abstract: The energetic demands of stressors like parasitism require hosts to reallocate energy away from normal physiological processes to survive. Life history theory provides predictions about how hosts will reallocate energy following parasitism, but few studies provide empirical evidence to test these predictions. We examined the sub-lethal effects of sea lamprey parasitism on lean and siscowet lake charr, two ecomorphs with different life history strategies. Leans are shorter lived, faster growing, and reach reproductive maturity earlier than siscowets. Following a parasitism event of 4 days, we assessed changes to energy allocation by monitoring endpoints related to reproduction, energy storage, and growth. Results indicate that lean and siscowet lake charr differ considerably in their response to parasitism. Severely parasitized leans slightly increased their reproductive effort and maintained growth and energy storage, consistent with expectations based on life history that leans are less likely to survive parasitism and have shorter lifespans than siscowets making investing in immediate reproduction more adaptive. Siscowets nearly ceased reproduction following severe parasitism and showed evidence of altered energy storage, consistent with a strategy that favors maximizing long-term reproductive success. These findings suggest that life history can be used to generalize stressor response between populations and can aid management efforts.